The performance of a fiber optic displacement sensor for different types of probes and targets - Yasin, M.; Harun, S.W.; Abdul-Rashid, H.A.; Kusminarto, Kusminarto; Karyono, Karyono; Ahmad, H. (WILEY-V C H VERLAG GMBH, 2008)
A simple fiber optic displacement sensor is presented using a multimode plastic bundled fiber and the intensity modulation technique. The preformance of the sensor is compared for different types of probes and targets. The probe with the largest receiving core diameter demonstrates the highest linearity range, and increasing the number of receiving cores increases the sensitivity of the sensor. With a stainless steel target and the concentric bundled fiber with 16 receiving fibers as aprobe, the sensitivity of the sensor ois found to be 0.0220 mV/mu m over 150 to 550 mu m range and -0.0061 mV/mu m over 1100 to 2000 mu m range. The target with a higher reflectivity shows a higher sensitivity. The linearity range for the front slope is almost similar for all targets tested. However, for the back slope, lower reflectivity objects have a relatively higher linearity range with the highest range of 1600 mu m being obtained using plastic and aluminum targets. The simplicity of the design, high degree of sensitivity, dynamic range, non-contact measurement and low cost of the fabrication make it suitable for applications in industries for position control and micro displacement measurement in the hazardous regions.